2021
DOI: 10.1155/2021/5560443
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Artificial Aging on the Antifungal Activity of PMMA Denture Base Material Modified with ZrO2 Nanoparticles

Abstract: The antifungal effect of zirconium dioxide nanoparticles (ZrO2NPs) incorporated into denture base material has been inadequately investigated; additionally, to the authors’ knowledge, no studies have assessed the influence of artificial aging on the antifungal activity of these particles. Methodology. Heat-polymerized acrylic resin disks were fabricated and divided into four groups (0%, 1%, 2.5%, and 5% ZrO2NPs by weight). Antifungal activity was assessed using the direct culture and disk diffusion methods. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Hamid et al investigated the effect of adding ZrO 2 NPs to PMMA denture base acrylic resin to inhibit and/or treat denture stomatitis and they found that this incorporation had a significant long-term antifungal effect [ 30 ]. In contrast, another study by Abualsaud et al found insignificant effect of ZrO 2 NPs on the reduction of Candida albicans biofilm formation [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hamid et al investigated the effect of adding ZrO 2 NPs to PMMA denture base acrylic resin to inhibit and/or treat denture stomatitis and they found that this incorporation had a significant long-term antifungal effect [ 30 ]. In contrast, another study by Abualsaud et al found insignificant effect of ZrO 2 NPs on the reduction of Candida albicans biofilm formation [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of nanoparticle additives for strengthening the bases of dental prostheses is now widely discussed [23,24,[35][36][37]. A recent systematic review by Gad et al, showed an improvement in the repaired dentures' mechanics, thanks to the use of nano-ZrO 2 , nano-SiO 2 and nano-Al 2 O 3 [23].…”
Section: General Interpretation Of the Resultsmentioning
confidence: 99%
“…A digital caliper with 0.01 mm accuracy was utilized to assess the specimens’ dimensions. Afterward, specimens were stored in distilled water at 37 °C for 7 days [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…3D-printed specimens (8 × 7 × 30 mm 3 ) were fabricated utilizing an acrylate ester-based resin (NextDent Denture 3D+, 3D systems, Vertex Dental B.V., Soesterberg, The Netherlands) and a 3D printer (NextDent 5100, 3D systems, Vertex Dental B.V., Soesterberg, The Netherlands) at a 90° orientation, layer-by-layer (50 μm/layer), in a straight-lined pattern [ 17 ]. Following initial printing, the specimens were cleaned in an isopropyl alcohol solution as per the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%